2015
DOI: 10.1039/c4ra14330b
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect of sodium polystyrene sulfonate and guanidine hydrochloride on the surface properties of lysozyme solutions

Abstract: A study of the dilational surface viscoelastic properties of mixed solutions of lysozyme and denaturing agents with different chemical natures allows us to characterize the changes of protein tertiary structure in the surface layer upon adsorption at the liquid-gas interface. We show that guanidine hydrochloride (GuHCl) and urea influence the dynamic surface properties of lysozyme solutions less than the properties of previously studied solutions of bovine serum albumin and b-lactoglobulin. Although the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…Consequently, NR was often applied to polyelectrolyte/surfactant mixtures at airwater interfaces. 16,[39][40][41][42][43][44] In fact, the effect of the surfactant chain length on the thickness of NaPSS/CnTAB layers adsorbed to the air-water interface has been studied with NR by Taylor et al 14 However, they varied the surfactant concentration (as opposed to polyelectrolyte concentration in our work) and did not report on the differences in the binding behavior and the surface charge of polyelectrolyte-surfactant complexes at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, NR was often applied to polyelectrolyte/surfactant mixtures at airwater interfaces. 16,[39][40][41][42][43][44] In fact, the effect of the surfactant chain length on the thickness of NaPSS/CnTAB layers adsorbed to the air-water interface has been studied with NR by Taylor et al 14 However, they varied the surfactant concentration (as opposed to polyelectrolyte concentration in our work) and did not report on the differences in the binding behavior and the surface charge of polyelectrolyte-surfactant complexes at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no kinetic dependencies of the dynamic surface elasticity had local maxima, and they remained monotonic Fig. 2 , unlike the corresponding results for lysozyme/GuHCl solutions, where the local maxima were related to globule unfolding 27,31 . Thus, the lysozyme globular structure was probably mostly preserved in the surface layer.…”
Section: Resultsmentioning
confidence: 77%
“…Whereas the denaturation of the globular structures of bovine serum albumin and β-lactoglobulin occurs at lower denaturant concentrations in the surface layer than in the bulk phase, Perriman et al have observed the opposite behavior in lysozyme solutions . This result agrees with dilational surface rheology measurements. , The addition of strong denaturants to dilute lysozyme solutions leads to smoother changes of the kinetic dependencies of the dynamic surface elasticity than for solutions of other globular proteins, where strong peaks of the surface elasticity are observed. Moreover, the addition of urea does not change the shape of the corresponding kinetic curves up to very high concentrations of the denaturant (∼10 M) …”
Section: Introductionmentioning
confidence: 75%
“…In this case the adsorption is slow enough and the main steps of this process can be followed by measuring the kinetic dependencies of surface properties. 10,11 For reference, a description of the kinetic dependencies of the surface tension and the real part of the dynamic surface elasticity is given for solutions of hydrogenous lysozyme without addition of NaCl measured under dynamic conditions involving sinusoidal oscillations of the surface area ( Fig. 1).…”
Section: Lysozyme Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation